KIAT-KIAT PEMBERDAYAAN PERPUSTAKAAN SEKOLAH - Rosinar, Euis (Edulib, 2014)
AbstractA combination of expertsâ€™ idea-generating, dignitaries in librarianship, and decision makersâ€™ concerns at the level of Government should have been made capable of realizing libraries as the facilitator of teaching-learnig process with promising outcomes. Bright learners by way of efforts made in terms of an ever enhanced curriculum should have been developing to sophisticated personalities and geared towards humans with qualities. What has gone in practice proves to be swerving to some extent in that some sort of comprehensive model of running library services is due needed: a standing structure built in the middle of the scholl; collections including books, non-books, digital; and truly Librarian (i.e. main manager of the intellectual asset). Any most interesting activities possible need to be created to make library an area of â€œplayâ€ being the goal of a means to accelerating a reading habit especially among children in their early age. The librarianâ€™s new paradigm should manage to penetrate the academic area of teachers in order that their collaboration with the teaching staff gives the chance to the libraryâ€™s functioning in an optimal way.Keywords: School library, school library design, school library activitiesÂ ABSTRAKPerpaduan rancang-gagas pakar, dignitary kepustakawanan, dan decision makers pada tataran Pemerintah seharusnya telah mewujudkan perpustakaan sebagai fasilitas proses belajar-mengajar yang mumpuni. Pembelajar yang dicerdaskan oleh upaya pencanggihan kurikulum sekolah seyogianya bertumbuh menjadi pribadi yang unggul dan berkembang ke arah insan yang berkualitas. Kenyataan di lapangan saat ini memerlukan suatu model menyeluruh penyelenggaraan perpustakaan: gedung yang berdiri tegap ditengah-tengah sekolah; koleksi buku, non-buku, digital; dan Pustakawan (baca: pengelola utama aset intelektual) seutuhnya. Kegiatan-kegiatan menarik harus dikreasikan untuk menjadikan perpustakaan sebagai area â€œbermainâ€ yang dimaksudkan sebagai ajang penumbuhan minat baca terutama pembelajar usia dini. Paradigma baru Pustakawan selayaknya merambah ke wilayah akademik pengajar agar kolaborasinya kelak berimbas pada berfungsinya perpustakaan secara optimal.Kata kunci: Perpustakaan sekolah, tata ruang perpustakaan sekolah, kegiatan perpustakaan sekolah